Kai kurios dzūkavimo raidos tendencijos Pelesos šnektoje - Trumpa, Edmundas (Baltistica, 1998)
SOME TENDENCIES OF THE DEVELOPMENT OF DZUKIAN ELEMENTS IN THE PELESA LOCAL DIALECT The whistling affricates c̑, ʒ̑ have been noticed to disappear in the Lithuanian local dialect in and around Pelesa (Voronov district, Byelorus), a subdialect of Southern aukštaičiai. This innovation, which can also be observed in other dialects contacting with the Slavs, is being stimulated not by Standard Lithuanian, but by the adopted Byelorussian articuliation basis of the younger generation, the decaying consonant timbre correlation. In the said local dialect the alveolar consonants /š/, /ž/, /r/ have no palatalized correlates. This creates favourable conditions for the palatalized correlates of the dental consonants /s/, /z/ to acquire the features of the hushing ś, ź instead of the whistling allophones s̑, z̑ and in this way to induce the pronunciation of less velarized non-palatalized ɫ, n. The process, which first affects fricatives, can be considered to be the beginning of the disappearance of timbre correlation in the phonological system of the sub-dialect, i.e. a process when palatalized consonants become palatal. Meanwhile the assibilated fricative element has not turned yet into hushing, in most cases, and the whistling affricates are still heard. The resistance to alveolarization can be accounted for by the fact the affricates are not known to have ever belonged to the timbre correlation. Only the disappearance of the opposition of non-palatalized and palatalized consonants can stimulate the development of old palatalized sounds. In fact the speech of all representatives of the local dialect contains intermediary affricates with an alveolarized fricative element and some completely new sounds, which leads to the following process: – the first type of speaking with a Dzūkai accent c̑Vu̇> ćVu̇> čVu – the second type of speaking with a Dzūkai accent c̑V i> ćV i > t́ sV> t́V i The difference between these two types can be interpreted as a nieder phonological process: in the neutralization position the allophones of the new phonemes /t’/, /d’/ are being reinforced. In the system of the local dialect palatized dental consonants are pushed out by palatalized alveolar ones.